2013
DOI: 10.1016/j.joca.2013.02.371
|View full text |Cite
|
Sign up to set email alerts
|

Variation in osteoarthritis biomarker serum comp levels in Mexican Americans is associated with SNPs in a region of chromosome 22q encompassing MICAL3, BCL2L13, and BID

Abstract: Acetylated-Histone 3 (A-H3) level was increased upon treatment with all 4 HDIs, consistent with effective suppression of HDAC activity. The most effective specific HDI was MS275, which showed similar A-H3 levels to TSA, but exhibited some undesirable effects of pan-HDI. PCI increased A-H3 levels, though not as effective as MS275, but also reduced the negative effects of TSA, such as decreased COX-2 and MMP-3 expression under treatment with IL1b. Also, the additive effect of TSA and IL1b on the secretion of MMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Apoptosis-induced morphological changes have been observed in the chondrocytes in degenerative cartilage, suggesting a pathway for OA pathology [ 35 ]. Our findings are consistent with those of another study that revealed that BCL2L13, a proapoptotic member of the BCL-2 family of apoptosis protein, plays a role in the mitochondrial apoptosis pathway, which is altered in OA [ 36 ]. By upregulating BCL2L13 expression, the long noncoding RNA SNHG15 can inhibit OA progression [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…Apoptosis-induced morphological changes have been observed in the chondrocytes in degenerative cartilage, suggesting a pathway for OA pathology [ 35 ]. Our findings are consistent with those of another study that revealed that BCL2L13, a proapoptotic member of the BCL-2 family of apoptosis protein, plays a role in the mitochondrial apoptosis pathway, which is altered in OA [ 36 ]. By upregulating BCL2L13 expression, the long noncoding RNA SNHG15 can inhibit OA progression [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…Of notice, two apoptosis-related genes were identified this way in TAR, BCL2L13 (BCL2 like 13), and ATRAID (All-Trans Retinoic Acid-Induced Differentiation Factor). The former encodes for a pro-apoptotic protein that localizes in the mitochondria and is highly expressed in skeletal muscle (GTEx release V7) and is found in a locus previously associated to osteoarthritis (OA) risk in Mexican Americans (Coan et al 2013). ATRAID (alternative name APR-3, apoptosis-related protein 3), is thought to be involved in apoptosis hematopoietic development and differentiation, and in positive regulation of bone mineralization and osteoblast differentiation (Zou et al 2011).…”
Section: Population-specific Adaptive Evolution Within Mexicomentioning
confidence: 99%